The rights of the LGBTIQ+ community within the universal system of human rights protection. A legal analysis through the human rights-based approach - Martínez Ventoso, Santiago (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2024)
Arising from the fact that the LGBTQI+ community suffers a context of systemic discrimination and oppression, this article aims at responding to this situation from the universal system of the protection of the rights. To do so, the principles of equality and non-discrimination are the starting points from which a human-rights based approach is justified as the suitable methodology to do both a revision of the existing provisions applicable to the LGBTIQ+ community and a proposal of change, which includes the enacting of a specific provision as the mean to correct this situation.